Examining the Impact of Women's Savings Groups on Socio¬economic Welfare of Families in Northern Division Kabale Municipality. - Namara, Brenda (Kabale University, 2024)
Saving groups including women's savings groups are promoted by numerous international and local Non-Governmental Organisations, government agencies and microfinance institutions in Uganda as a strategy for poverty eradication and improving the socio-economic welfare of families mostly among low-income earners (Agnes & Ruth, 2017). The government of Uganda through its programmes like the "bonabagagawale" scheme, the microfinance movement schemes, the parish development model and other government programmes strongly emphasises that the poor people including women participate in savings and self-help groups, not as individuals if they are to benefit from such programmes (Hassan, 2018). These savings groups, help women to own projects, and train their members, they offer soft loans, act as collateral to fellow members and are more often associated with the improvement of individual members both economically and socially. Despite the existence of women's savings groups in the Northern division of Kabale Municipality which would help in poverty reduction and improve on socio-economic welfare of families through the provision of small loans to its members at low interest rates and saving the little they have, still, the social economic welfare of families has remained the same in the area and there seem to be no reasons for forming such savings groups. The purpose of the study was to examine the impact of women's savings groups on the socioeconomic welfare of families in the Northern division of Kabale Municipality.